Oropharyngeal pH Testing Does Not Predict Response to Proton Pump Inhibitor Therapy in Patients with Laryngeal Symptoms. (November 2016) - Yadlapati, Rena; Pandolfino, John E; Lidder, Alcina K; Shabeeb, Nadine; Jaiyeola, Diana‐Marie; Adkins, Christopher; Agrawal, Neelima; Cooper, Andrew; Price, Caroline P E; Ciolino, Jody D; Gawron, Andrew J; Smith, Stephanie S; et al.
Abstract : Objectives: Predicting response to proton pump inhibitor (PPI) therapy in patients with laryngeal symptoms is challenging. The Restech Dx‐pH probe is a transnasal catheter that measures oropharyngeal pH. In this study, we aimed to investigate the prognostic potential of oropharyngeal pH monitoring to predict responsiveness to PPI therapy in patients with laryngeal symptoms. Methods: We conducted a physician‐blinded prospective cohort study at a single academic institution between January 2013 and October 2014. Adult patients with Reflux Symptom Index scores (RSI) ≥13 off PPI therapy were recruited. Patients underwent video laryngoscopy and 24‐h oropharyngeal pH monitoring, followed by an 8‐ to 12‐week trial of omeprazole 40 mg daily. Prior to and following PPI therapy, patients completed various symptom questionnaires. The primary outcome was the association between PPI response and oropharyngeal pH metrics. PPI response was separated into three subgroups based on the post‐treatment RSI score and % RSI response: non‐response=RSI ≥13; partial response=post‐treatment RSI <13 and change in RSI <50%; and complete response=post‐treatment RSI <13 and change in RSI ≥50%. The primary analysis utilized a multinomial logistic regression controlling for the pre‐treatment RSI score. A secondary analysis assessed the relationship between the change in RSI (post–pre) and oropharyngeal pH metrics via ordinary least square regression. Results: Thirty‐four patients completed the study and were included in final analysis. Symptom response to PPI therapy was as follows: 50% no response, 15% partial response, and 35% complete response. Non‐responders had a higher pre‐treatment RSI ( P <0.01). There were no significant differences in oropharyngeal acid exposure (below pH of 4.0, 5.0, 5.5, 6.0, and RYAN scores) between responder types. The secondary analysis noted a trend between lower PPI response and a greater total percent time below pH of 5.0 ( P =0.03), upright percent time below pH of 5.0 ( P =0.07), and RYAN supine (corrected; P =0.03), as well as an association between PPI response and greater decreases in the Anxiety Sensitivity Inventory ( P <0.01), Brief Symptom Inventory‐18 ( P <0.01), and Negative Affect Scale ( P <0.01). Conclusions: Oropharyngeal pH testing did not predict laryngeal symptom response to PPI therapy. Contrary to hypothesis, our study signaled that the degree of oropharyngeal acid exposure is inversely related to PPI response. In addition, reduction in negative affect and psychological distress parallels PPI response.